Variation in Hematological Indices, Oxidative Stress, and Immune Function Among Male Song Sparrows From Rural and Low-Density Urban Habitats - Goodchild, Christopher G.; VanDiest, Isaac; Lane, Samuel J.; Beck, Michelle; Ewbank, Hallum; Sewall, Kendra B. (Frontiers in Ecology and Evolution, 2022)
A central theme in the field of ecology is understanding how environmental variables influence a species’ distribution. In the last 20 years, there has been particular attention given to understanding adaptive physiological traits that allow some species to persist in urban environments. However, there is no clear consensus on how urbanization influences physiology, and it is unclear whether physiological differences in urban birds are directly linked to adverse outcomes or are representative of urban birds adaptively responding to novel environmental variables. Moreover, though low-density suburban development is the fastest advancing form of urbanization, most studies have focused on animals inhabiting high intensity urban habitats. In this study, we measured a suite of physiological variables that reflect condition and immune function in male song sparrows (Melospiza melodia) from rural and suburban habitats. Specifically, we measured hematological indices (packed cell volume [PCV], hemoglobin concentration, mean corpuscular hemoglobin [MCHC]), circulating glutathione (total, reduced, and oxidized), oxidative damage (d-ROM concentration), antioxidant capacity, and components of the innate immune system (bacteria killing ability [BKA], white blood cell counts). We also measured whole-animal indices of health, including body condition (mass/tarsus length) and furcular fat. Song sparrows inhabiting suburban environments exhibited lower hemoglobin and MCHC, but higher body condition and furcular fat scores. Additionally, suburban birds had higher heterophil counts and lower lymphocyte counts, but there were no differences in heterophil:lymphocyte ratio or BKA between suburban and rural birds. PCV, glutathione concentrations, and oxidative damage did not differ between suburban and rural sparrows. Overall, suburban birds did not exhibit physiological responses suggestive of adverse outcomes. Rather, there is some evidence that sparrows from rural and suburban habitats exhibit phenotypic differences in energy storage and metabolic demand, which may be related to behavioral differences previously observed in sparrows from these populations. Furthermore, this study highlights the need for measuring multiple markers of physiology across different types of urban development to accurately assess the effects of urbanization on wildlife.